A meta-analysis of continuous positive airway pressure therapy in prevention of cardiovascular events in patients with obstructive sleep apnoea. (24th October 2017) - Khan, Safi U; Duran, Crystal A; Rahman, Hammad; Lekkala, Manidhar; Saleem, Muhammad A; Kaluski, Edo
Abstract: Aims: To assess whether continuous positive airway pressure (CPAP) therapy reduces major adverse cardiovascular events (MACE) in patients with moderate-to-severe obstructive sleep apnoea (OSA). Methods and results: A total of 235 articles were recovered using MEDLINE, EMBASE and Cochrane library (inception–December 2016) and references contained in the identified articles. Seven randomized controlled trials (RCTs) were selected for final analysis. Analysis of 4268 patients demonstrated non-significant 26% relative risk reduction in MACE with CPAP [risk ratio (RR) 0.74; 95% confidence interval (CI) 0.47–1.17; P = 0.19, I 2 = 48%]. A series of sensitivity analyses suggested that increased CPAP usage time yielded significant risk reduction in MACE. and stroke. Subgroup analysis revealed that CPAP adherence time ≥4 hours (h)/night reduced the risk of MACE by 57% (RR 0.43; 95% CI 0.23–0.80; P = 0.01, I 2 = 0%). CPAP therapy showed no beneficial effect on myocardial infarction (MI), all-cause mortality, atrial fibrillation/flutter (AF), or heart failure (HF) ( P > 0.05). CPAP had positive effect on mood and reduced the daytime sleepiness [Epworth Sleepiness Scale (ESS): mean difference (MD) −2.50, 95% CI − 3.62, −1.39; P < 0.001, I 2 = 81%]. Conclusion: CPAP therapy might reduce MACE and stroke among subjects with CPAP time exceeding 4 h/night. Additional randomized trials mandating adequate CPAP time adherence are required to confirm this impression.